Evidence for coordination of lysosomal (ASMase) and plasma membrane (NSMase2) forms of sphingomyelinase from mutant mice - Qin, Jingdong (2012)
NSMase2 is associated to the plasma membrane, whereas ASMase is predominantly lysosomal; both hydrolyze sphingomyelin (SM) to ceramide and phosphocholine. Although SM accumulated in both ASMase(-/-) and fro/fro (NSMase2(-/-)) fibroblasts, the reduction of ceramides was more dramatic in fro/fro cells. ASMase mRNA, protein and enzyme activity were substantially elevated in fro/fro fibroblasts. In contrast, NSMase2 activity was unaffected in ASMase(-/-) fibroblasts. ASMase(-/-) cells showed normal cell cycling whereas fro/fro cells grew slowly and were arrested in G1/G0 and could be corrected by transfection with smpd3 gene. This suggests two distinct subcellular pathways for SM catabolism with distinct functions.